Legal Characteristics of Electronic Justice as Project of Electronic Democracy in the Context of the International Practice and Influence of Electronic Justice on Ensuring Independence and Impartiality of Bodies of Judicial Authority - Yaroslav Valeryevich Antonov (Управленческое консультирование, 2018)
There are various forms and legal mechanisms for e-democracy. It includes an e-justice. E-justice is characterized by transparency, accountability, transparency of information, provision of electronic document. In this paper the author examines the prospects the influence of e-justice in the impartiality and independence of arbitrators. The author notes that e-democracy is becoming increasingly important trend in the world legal and political practice. In 2009, the European Council has identified in it recommendation the role and place of e-democracy, as a means to strengthen the existing system of democracy by increasing public participation and access to the democratic processes. As one of the areas of e-democracy, the Council of Europe highlighted the electronic system of justice. E-justice involves the creation of a transparent, accountable and independent judiciary based on the electronic workflow. Issues of impartiality and independence of arbitrators and the judiciary are critical to any kind of litigation. Ensuring an impartial and independent judicial proceedings, as in the system of arbitration courts and in the state courts of arbitration is often considered by scholars as a factor of investment attractiveness for business, after all, impartial and independent trial obviously gives us confidence in the future. The author in this paper assess the legal perspectives of e-justice in ensuring the impartiality and independence of arbitrators in the terms of international experience and the legal position of the European Court of Human Rights. The author notes that the development of e-justice system in Russia is in general at an early stage. Nevertheless, quite clearly observed a trend “dematerialization” of the trial and the shifting of a number of stages of the proceedings in the electronic channel. In this regard, the study of foreign experience of development of e-justice, in my opinion, is very important. The article also studied the legal characteristics of e-justice with influence as to ensure the impartiality and independence of arbitrators, and the development of e-justice as a whole, providing quality uniform legal regulation in this area.